A fish-specific antimicrobial peptide MsPiscidin2 inactivates MSRV and confers protection in largemouth bass - Fei, Chenjie; Wang, Ziwen; Hu, Yang; Nie, Li; Chen, Jiong (Frontiers in Immunology, 2025)
Antimicrobial peptides (AMPs) represent an evolutionarily conserved component of innate immunity with broad-spectrum antimicrobial and antiviral activities. However, the antiviral potential of fish-specific piscidins against emerging aquatic viruses largely remains to be explored. In this study, we evaluated the antiviral properties of three piscidins (designated here as MsPiscidin1, MsPiscidin2 and MsPiscidin3) identified from largemouth bass (Micropterus salmoides) against Micropterus salmoides rhabdovirus (MSRV), a major pathogen causing high mortality in farmed largemouth bass. Computational prediction and expression profiling revealed inducible expression of MsPiscidins upon MSRV infection, with distinct tissue-specific patterns. Functional assays demonstrated that while MsPiscidin1 and MsPiscidin3 primarily modulated host antiviral responses, MsPiscidin2 exhibited direct virucidal activity against MSRV. Molecular docking predicted potential interactions between MsPiscidin2 and the MSRV glycoprotein, where histidine and glutamic acid residues of MsPiscidin2 are positioned in close proximity to cysteine and methionine residues of the MSRV glycoprotein, supporting its capacity to directly target viral particles. In vitro assays further confirmed that MsPiscidin2 significantly suppressed MSRV replication and attenuated cytopathic effects in a dose-dependent manner. Further, MsPiscidin2 treatment conferred significant in vivo protection, delaying disease progression and improving survival rates in MSRV-infected juvenile bass. These findings provide the first evidence of piscidin-mediated antiviral defense against MSRV and highlight MsPiscidin2 as a promising candidate for developing novel antiviral strategies in largemouth bass aquaculture.